Icelandic National Culture in Relation to Hofstede´s Five Dimensions - Aðalsteinsson, Gylfi Dalmann; Guðmundsdóttir, Svala; Guðlaugsson, Þórhallur (Stjórnsýslustofnun, 2011)
According to the cultural literature, societies are composed from many different culturally dissimilar countries (Hofstede, 2001; House et al., 2004). Geert Hofstede is one of many researchers who had developed a method to measure national culture. His research on national culture has had a great impact on how we understand and measure different culture differences. The purpose of this research is to investigate the characteristics of Icelandic national culture and compare with Bearden et.al. (2006) findings, where data was used from university students from four countries, Argentina, Austria, Japan and USA. In this study undergraduate students from the school of Social Science at the University of Iceland were asked to answer a questionnaire (VSM 94) and a total of 427 responses were usable with the response rate of 15%. According to the results, Icelandic national culture can be characterized by low power distance (PDI), high individualism (IDV), low masculinity (MAS), high uncertainty-avoidance (UAI) and average long-term orientation (LTO). Rannsóknir Geert Hofstede á þjóðmenningu og framsetning hans á stjórnun innan ólíkra menningarheima hefur haft mikil áhrif á skilning manna á mismunandi menningu skipulagsheilda í ólíkum löndum. Þannig hafa menn öðlast meiri skilning á menningarlegum mismun skipulagsheilda sem hefur haft mikil áhrif á stjórnunarfræðin. Í þessari rannsókn er leitast við að svara því hver séu einkenni þjóðmenningar á Íslandi út frá víddum Hofstede og hver þessi einkenni eru samanborin við sambærilegt úrtak í fjórum löndum. Ástæðan fyrir vali á úrtaki eru tvíþættar. Annars vegar er lögð áhersla á að úrtakið sé eins einsleitt og hægt er (Hofstede, 1994) og því lágmarks breytileiki hvað varðar aldur, menntun, tekjur og aðrar bakgrunnsbreytur og hins vegar er leitast við að velja úrtak til að gera rannsóknina samanburðarhæfa við rannsókn Bearden, Money og Nevins (2006) en þar var unnið með gögn frá háskólanemum í fjórum löndum Argentínu, Austurríki, Japan og Bandaríkjunum. Spurningalisti (VSM ...